Noncollinear magnetism of Cr and Mn nanoclusters on Ni(111): Changing the magnetic configuration atom by atom - Lounis, Samir; Mavropoulos, Phivos; Zeller, Rudolf; Dederichs, Peter H.; Blügel, Stefan (PHYSICAL REVIEW B, 2007)
The Korringa-Kohn-Rostoker Green-function method for noncollinear magnetic structures was applied on Mn and Cr nanoclusters deposited on the Ni(111) surface. We consider various dimers, trimers, and tetramers. We obtain collinear and noncollinear magnetic solutions, brought about by the competition of antiferromagnetic interactions. It is found that the triangular geometry of the Ni(111) substrate, together with the intracluster antiferromagnetic interactions, is the main cause of the noncollinear states, which are secondarily affected by the cluster-substrate exchange interactions. The stabilization energy of the noncollinear, compared to the collinear, states is calculated to be typically of the order of 100 meV/atom, while multiple local-energy minima are found, corresponding to different noncollinear states, differing typically by 1-10 meV/atom. Open structures exhibit sizable total moments, while compact clusters tend to have very small total moments, resulting from the complex frustration mechanisms in these systems.